The importance of music in the learning of a child with multiple disabilities (Research, Society and Development, 2021)
The study aimed to investigate the importance of music in the learning of a child with multiple disabilities, seeking to identify vocabulary acquisitions, verifying the interaction with other people in the school environment and certifying the repercussions in the family context. It sets up a case study, developed in an educational institution for people with visual impairment, according to the observations of communication and interaction difficulties of a student with multiple disabilities (Down Syndrome, ASD-Autistic Spectrum Disorder and low visual impairment vision) came from this study. The methodology associated practical music classes in the light of the interactionist view, with support in popular songs and the child's daily life, in which breathing and relaxation exercises were performed, activities involving the exploration of body sounds, the manipulation of band instruments, the coordination of rhythmic movement with verbal expression following a sequence, the execution of tempo, imitation and variations in speed. In dialogue with authors of pedagogy and music education, music was perceived as an excellent facilitator in the student's learning, new words were added to the vocabulary, related to the songs learned, it also favored social inclusion and contributed to a significant improvement in the ability to expression, relationship, expansion of the sense of overcoming and raising self-esteem. It is inferred, therefore, that music is an excellent means of contributing to the development of all individuals, in the context of educating participants with disabilities, it is necessary to adopt specific methodologies aimed at meeting individual demands.